Low-Cost Carriers Socio-Economic Impact in Tourism Development: The Case of Faro’s Airport Hinterland - Rosado, Tiago (2020)
Submitted by Jorge Miguel Reis Silva (jmrs@ubi.pt) on 2020-02-12T11:15:10Z No. of bitstreams: 1 Tourism Spectrum-2017.pdf: 361027 bytes, checksum: e039bd6f3967724a9414184c6cb6747d (MD5)